2022
DOI: 10.1177/2164957x221100468
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Forest Therapy on Work-Related Stress for Employees in the Manufacturing Industry: Randomized Control Study

Abstract: Background The effect of a forest therapy in a natural environment noted that the forest therapy induced a state of relaxation among workers, thereby decreasing cortisol levels and work-related stress. Objective The primary objective of this study is to determine the effects of the forest therapy for employees in the manufacturing industry on psychological stress responds, stress hormone and heart rate variability (HRV). The secondary objective is to determine the effects of the forest therapy for employees in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Studies indicated that after forest bathing, POMS scores for participants on the ve negative subscales signi cantly decreased [4,11,12], reduced anxiety [8,11,13], tension [14], and stress [11], increased mindfulness [15], optimized social connection [8, 15,16], positive affect [11,15], connection with nature [4,11], compassion for oneself [11], depressive symptoms [6,11,14,15,17,18], negative emoticons [16,19], the cardioprotective effect [13], and sleep [14]. Regarding vigor, four studies indicate that it increased [13,14,16,17], and two other studies indicate that it did not vary signi cantly [8,20].…”
Section: Methodology A) Bibliographic Research Stagementioning
confidence: 99%
“…Studies indicated that after forest bathing, POMS scores for participants on the ve negative subscales signi cantly decreased [4,11,12], reduced anxiety [8,11,13], tension [14], and stress [11], increased mindfulness [15], optimized social connection [8, 15,16], positive affect [11,15], connection with nature [4,11], compassion for oneself [11], depressive symptoms [6,11,14,15,17,18], negative emoticons [16,19], the cardioprotective effect [13], and sleep [14]. Regarding vigor, four studies indicate that it increased [13,14,16,17], and two other studies indicate that it did not vary signi cantly [8,20].…”
Section: Methodology A) Bibliographic Research Stagementioning
confidence: 99%
“…More than half of the studies were single-group trials with pre-and post-tests (n = 9). Seven studies were two-group trials while four used a randomized controlled trial (RCT) [38,60,68,70]. One study used a two-period crossover design [69].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In recent years, nature immersion therapies have emerged as alternative approaches to alleviating stress, depression, and anxiety [ 11 , 12 , 13 ]. These therapies leverage exposure to natural environmental stimuli to induce physiological relaxation, potentially enhancing immune functions and aiding in disease prevention [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%